Teaching Methods for Promotion of Social Justice Competences in Religious Studies Among Students in Selected Leribe Secondary Schools - Kurata, Lehlohonolo (Eastasouth Institute, 2025)
Many countries are revising their educational curricula to better address pressing global issues like social injustice and oppression. This includes incorporating social justice themes into Religious Studies classes to foster awareness and action among students. Despite this global trend, research on the integration of social justice into Religious Studies curriculum in Lesotho remains limited. This research, based on critical theory, investigates the influence of Religious Studies teaching methods on the development of social justice competences among secondary school students in Leribe, Lesotho. The study used a qualitative case study design. Six Religious Studies instructors from three church-owned secondary schools were specifically chosen. Data was collected through lesson observations and analysed using thematic analysis. The findings indicate that Religious Studies teachers use interactive discussions, group work, and contextual analysis, to significantly enhance critical thinking and inclusivity, thereby fostering social justice competences. However, challenges were noted, such as resource limitations in particular, a lack of Bibles in some schools, and inconsistent learner engagement, particularly in lessons relying heavily on recall-based questioning. To address these challenges, the study recommends integrating Religious Studies materials into government book-rental schemes and offering continuous teacher training to support innovative teaching methods. While the current pedagogical approaches present significant opportunities for developing social justice competences, addressing resource and engagement issues is crucial for maximising their effectiveness.